2008
DOI: 10.1038/pcan.2008.20
|View full text |Cite
|
Sign up to set email alerts
|

Distress and social dysfunction following prostate cancer treatment: a longitudinal cross-cultural comparison of Japanese and American men

Abstract: We assessed the impact of bother with urinary and bowel dysfunction on social activities among men in Japan and the United States following primary therapy for localized prostate cancer. In paired longitudinal outcomes studies, we measured general and disease-specific health-related quality of life in 400 Japanese and 427 American men who underwent radical prostatectomy or brachytherapy for localized prostate cancer. Outcomes included the social function domain of the Medical Outcomes Study Short Form-36 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Namiki et al also reported the impact of bother with urinary and bowel dysfunction on social activities among men in Japan and the USA after radical prostatectomy or brachytherapy for localized prostate cancer. 52 They found that the bother associated with both dysfunctions after surgery or brachytherapy for prostate cancer had a greater impact on social function in American men than in Japanese men. In another study, Taoka et al examined Japanese localized prostate cancer patients treated with radical prostatectomy, brachytherapy and external radiation therapy.…”
Section: Narrative Reviewmentioning
confidence: 99%
“…Namiki et al also reported the impact of bother with urinary and bowel dysfunction on social activities among men in Japan and the USA after radical prostatectomy or brachytherapy for localized prostate cancer. 52 They found that the bother associated with both dysfunctions after surgery or brachytherapy for prostate cancer had a greater impact on social function in American men than in Japanese men. In another study, Taoka et al examined Japanese localized prostate cancer patients treated with radical prostatectomy, brachytherapy and external radiation therapy.…”
Section: Narrative Reviewmentioning
confidence: 99%